2016
DOI: 10.1038/ncomms11240
|View full text |Cite
|
Sign up to set email alerts
|

Airway bacteria drive a progressive COPD-like phenotype in mice with polymeric immunoglobulin receptor deficiency

Abstract: Mechanisms driving persistent airway inflammation in chronic obstructive pulmonary disease (COPD) are incompletely understood. As secretory immunoglobulin A (SIgA) deficiency in small airways has been reported in COPD patients, we hypothesized that immunobarrier dysfunction resulting from reduced SIgA contributes to chronic airway inflammation and disease progression. Here we show that polymeric immunoglobulin receptor-deficient (pIgR−/−) mice, which lack SIgA, spontaneously develop COPD-like pathology as they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 52 publications
9
90
0
1
Order By: Relevance
“…This study is complementary to our recently published work showing that mice with a defective SIgA immune system in the lungs develop a COPD-like phenotype as they age with airway wall remodeling, an influx of macrophages and neutrophils, bacterial invasion across the epithelial barrier, and activation of NF-kB (17). All these findings were manifest in SIgA(2) airways in humans.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This study is complementary to our recently published work showing that mice with a defective SIgA immune system in the lungs develop a COPD-like phenotype as they age with airway wall remodeling, an influx of macrophages and neutrophils, bacterial invasion across the epithelial barrier, and activation of NF-kB (17). All these findings were manifest in SIgA(2) airways in humans.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with these observations, cultured airway epithelial cells from patients with COPD were reported to express lower levels of pIgR than airway epithelial cells from healthy control subjects (16). The importance of SIgA in COPD is further supported by our recent demonstration that pIgR-deficient mice, which cannot transcytose IgA to mucosal surfaces, develop a spontaneous COPD-like phenotype, including emphysema and fibrotic remodeling of small airways (17).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…54 This is consistent with the findings that targeting of the lung microbiota by innate immunity, as a result of pIgR/ sIgA deficiency, results in progressive small airway remodeling and emphysema. 55 Collectively, these observations support an emerging model that exposure of the pulmonary immune system to oral-derived microbiota (notably Prevotella spp.) during health is part of the central homeostatic processes that regulate pulmonary inflammatory responses.…”
Section: Lung Microbiota and Immunitymentioning
confidence: 61%
“…Recently, Richmond et al reported that polymeric immunoglobulin receptor-deficient mice, which lack secretory immunoglobulin A, spontaneously developed fragmentation of alveolar wall and small airway fibrosis with the activation of NF-κB associated with chronological aging [100]. These mice showed an altered lung microbiome, increased bacterial penetration into bronchial epithelium, enhanced macrophage accumulation, and increased MMP-12 levels [100].…”
Section: The Impacts Of Cellular Senescence In Age-related Lung DImentioning
confidence: 99%